The Effect of Using YouTube Video on the Tenth Graders' Writing Procedural Text Achievement at SMA Corpatarin - Sitorus, Carolina Junianti (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2017)
AbstractThis research was aimed to determine whether youtube video significantly effected the tenth graders’ writing procedural text achievement at SMA Corpatarin or not. This research was experimental research. The population of this research were 38 students and through random sampling method, control class (19 students) and experimental class (19 students) were taken. To attain the objective, data were colleted by the pre and post-test to both classes. The quantitavie data analysis was conducted with the SPSS version 17. To test the hypotheses, the researcher used normality test and homogeneity test. The results of the data analysis showed that the sample data of this research was normally distributed and homogeneous population variance and based on hypotheses test showed Sig.2-tailed (0.000) < Sig.level (0.05). It can be concluded that youtube video significantly affected the tenth graders’ writing procedural text achievement at SMA Corpatarin. Keyword: Youtube video, writing procedural text, experimental method